Cardiopulmonary Resuscitation: New Concept - Lee, Kwangha (The Korean Academy of Tuberculosis and Respiratory Diseases, 2012)
Cardiopulmonary resuscitation (CPR) is a series of life-saving actions that improve the chances of survival, following cardiac arrest. Successful resuscitation, following cardiac arrest, requires an integrated set of coordinated actions represented by the links in the Chain of Survival. The links include the following: immediate recognition of cardiac arrest and activation of the emergency response system, early CPR with an emphasis on chest compressions, rapid defibrillation, effective advanced life support, and integrated post-cardiac arrest care. The newest development in the CPR guideline is a change in the basic life support sequence of steps from "A-B-C" (Airway, Breathing, Chest compressions) to "C-A-B" (Chest compressions, Airway, Breathing) for adults. Also, "Hands-Only (compression only) CPR" is emphasized for the untrained lay rescuer. On the basis of the strength of the available evidence, there was unanimous support for continuous emphasis on high-quality CPR with compressions of adequate rate and depth, which allows for complete chest recoil, minimizing interruptions in chest compressions and avoiding excessive ventilation. High-quality CPR is the cornerstone of a system of care that can optimize outcomes beyond return of spontaneous circulation (ROSC). There is an increased emphasis on physiologic monitoring to optimize CPR quality, and to detect ROSC. A comprehensive, structured, integrated, multidisciplinary system of care should be implemented in a consistent manner for the treatment of post-cardiac arrest care patients. The return to a prior quality and functional state of health is the ultimate goal of a resuscitation system of care.